SHAP-Enhanced Multi-Class XG Boost for Early Detection and Risk Assessment of Cardiovascular Diseases - Puneetha, Annaldas; Laxminarayanamma, K.; Mohan Reddy, Ambati Rama; Noorullah, R.M. (Journal of Neonatal Surgery, 2025)
Cardiovascular diseases (CVDs) are a group of disorders affecting the heart and blood vessels, including coronary heart disease, cerebrovascular disease, and rheumatic heart disease. These conditions are among the leading causes of death globally. Traditional diagnostic methods often depend heavily on clinical expertise and can be time-consuming, which highlights the potential of machine learning as an effective alternative for faster and more accurate decision-making. This study employs a Multi-Class XG Boost model integrated with SHAP (SHapley Additive exPlanations) to predict the likelihood of cardiovascular diseases using a dataset comprising key demographic, clinical, and diagnostic features. The model achieved an accuracy of 86.59% on training data and 83.75% on testing data, demonstrating strong performance and robustness. The Multi-Class XG Boost approach allows the model to classify patients into multiple risk categories—such as low, medium, and high risk—rather than just binary outcomes (disease/no disease). This enhances the model’s clinical utility by providing a more granular prediction of disease severity. Additionally, the integration of SHAP enables interpretability by identifying how each feature (such as age, cholesterol level, blood pressure, or smoking status) contributes to the final prediction, making the model’s decisions more transparent to clinicians. In conclusion, the results suggest that the Multi-Class XG Boost model with SHAP not only provides high accuracy but also offers explainable and actionable insights for early detection and risk assessment of cardiovascular diseases. Future research could focus on expanding the dataset, exploring deep learning-based architectures, and enhancing model interpretability for real-time clinical applications